2018
DOI: 10.3390/educsci8040159
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Administrative Intensity and Student Retention and Success: A Three-Year Study

Abstract: Through the lens of complexity theory and by utilizing the methodological framework set forth in Gander’s 1999 article regarding internal and external organizational elements of administrative intensity, this secondary data analysis study linked the internal organizational elements of administrative intensity to institutional results as evidenced by higher education student retention and graduation rates. Representing institutional investments, efforts, and outcomes from 2004 to 2014, three years of data repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, we believe that a broader range of problem formulations should be considered, determined by the peculiarities of national legislation or the interests of various education stakeholders, as stated in reference [12]. For university administration, a generalized forecast is important, such as predicting whether a student will be expelled in the next semester [13]. For a course instructor, the forecast for the success of mastering the course is of interest [14].…”
Section: Formulations Of the Task Of Forecasting Learning Successmentioning
confidence: 99%
“…However, we believe that a broader range of problem formulations should be considered, determined by the peculiarities of national legislation or the interests of various education stakeholders, as stated in reference [12]. For university administration, a generalized forecast is important, such as predicting whether a student will be expelled in the next semester [13]. For a course instructor, the forecast for the success of mastering the course is of interest [14].…”
Section: Formulations Of the Task Of Forecasting Learning Successmentioning
confidence: 99%
“…They argued that large complex public organisations can benefit from allocating additional resources to administration as proposed by structural contingency theory. Romine et al (2018) examined the relationship between administrative intensity and student retention and success, and they found that aggregate faculty salary expenditure was positively related to student retention and that the proportion of full-time faculty members was also positively related to student retention. This suggests that the proportion of adjunct staff (equivalent to casual employees) is negatively correlated with student retention.…”
Section: Analytical Perspectives and Research Hypothesesmentioning
confidence: 99%
“…Consider in null hypothesis testing, a power analysis was completed and a specified number of research participants were determined to be needed to achieve the desired effect size and accepted Type II error. Within a Bayesian inference study, the sampling plan is not required to be specifically defined as to the number of participants needed, and a large sample will not have the same practical significance versus statistical significance problem that occurs in large sample sets (Kirk, 1996; Romine, Baker, & Romine, 2018). As time progresses, if additional data are acquired for the study, the Bayes factor can be used to monitor the evidence for either H0 or H1 until data collection is stopped or resources for the study have been expended (Andraszewicz et al, 2015).…”
Section: Bayesian Frameworkmentioning
confidence: 99%